Differences in the ultrastructure of two selected taxa of phytoplankton in a thermally stratified Lake Holzmaar (Germany) - Messyasz, Beata; Czerwik-Marcinkowska, Joanna; Lücke, Andreas; Uher, Bohuslav (Biodiversity: Research and Conservation, 2013)
This paper presents the results of ultrastructural studies and ecological aspects of some phytoplankton species belonging to the groups of cyanobacteria (Planktothrix rubescens, Synechocystis aquatilis) and green algae (Desmodesmus grahneisii). Specimens were collected during summertime from the mesotrophic and stratified Lake Holzmaar (Western Germany) as planktonic forms from the pelagic zone. The highest cyanobacterium concentration was detected in the metalimnion, where the alkaline pH, low phosphorus and high nitrogen contents were recorded. P. rubescens was characterized by straight filaments up to 1000 μm long and 5.4-8 μm wide and numerous aerotopes in cells. The accompanying algae were identified by ultrastructural analysis and photographic documentation was provided. In the case of D. grahneisii, chloroplast was situated in the parietal part of cell, with one large, oval pyrenoid and, in addition, the granular and spiny cell wall was an important taxonomical criterium for the Desmodesmus genus. This is in contrast with the cyanobacterium S. aquatilis, in which a homogeneous content with visible chromatoplasma was mostly distributed throughout the cell. This algal association was stable in the epilimnion characterized by the presence of high temperature, pH values (>8), nitrate nitrogen and oxygen concentrations